Cultural Dynamics and Ambidextrous Innovation: Insights from Saudi Arabia’s Project-Based Organizations—A Thematic–Explorative Study - Mohammad AlSaied; Patrick McLaughlin; Mohamed Afy-Shararah; John Patsavellas; Abdullah Alkhoraif (Administrative Sciences)
The implementation of ambidextrous innovation in project organizations within the cultures of the Global South, such as Saudi Arabia, is a significant problem. Organizational culture is positioned as a key factor that can help project organizations in cultures such as Saudi Arabia to implement ambidexterity as a key innovation framework. However, knowledge of ambidextrous innovations in such an important cultural and organizational context is highly limited. Thus, the aim of the present research is to explore key cultural aspects and themes based on action and a grounded theory research approach that can help organizations employ projects as a key work structure to implement ambidextrous innovations in project management offices (PMOs) in Saudi Arabia. To achieve this aim, the current study employed in-depth semi-structured interviews with 36 participants. The results, employing open coding procedures as a tool of data analysis using the NVivo 14.0 software package, revealed 62 key cultural aspects that can be critical in implementing the innovation of ambidexterity. To further validate and triangulate the findings, inter-rater reliability was undertaken with the help of two experts, and two sessions of focus group discussions were also conducted. The first session of the focus group helped us critically evaluate and filter the cultural aspects, resulting in the final 56 key cultural aspects. The second focus group session was undertaken with participants with the aim of grouping aspects into theoretical themes, which resulted in 10 themes. The research is novel in that it addresses both project organizations and the culture of the Global South, including Saudi Arabia. Empirical research needs to be conducted to predict and achieve other key outcomes.